Novel Applications and Technologies for the Industrial Exploitation of Algal Derived Marine Bioactives as Nutraceuticals or Pharmaceuticals - García-Vaquero, Marco; Tiwari, Brijesh K. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The active molecules or bioactives (i.e., polysaccharides, fatty acids, proteins, polyphenols, diterpenes, steroids and alkaloids) from algae (seaweed and microalgae) have been widely studied in recent years for multiple pharmaceutical and nutraceutical applications. Innovative and emerging technologies, including but not limited to ultrasounds, microwaves, electric fields, high-pressure supercritical fluids, ionic fluids and plasma, are currently being explored throughout multiple stages of the pre-treatment, extraction, isolation/purification and preservation of biomolecules from algae. This Special Issue will target research papers, reviews, short communications and perspectives on the use of novel technologies for the pre-treatment, extraction, isolation‒purification, characterization and preservation of marine compounds from algae. It will particularly focus on novel research related to algal bioactives with clear and demonstrated industrial applications and focuses.